ECONOMIC ESSENCE AND COMPOSITION OF THE RESOURCE POTENTIAL OF THE ENTERPRISE - MAZUR, Oleksandr; MAZUR, Dmytro; BETLINSKYI, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The authors of the article considered the issue of increasing the resource potential of the enterprise, its economic essence and composition. Aspects of production organization and design, the goal of every enterprise manager in the conditions of the modern market, which reveals the instability of economic data, are considered. The floating capabilities of the enterprise and plans for the future have been assessed and determined. The balance of the company's plans with the potential of external factors to achieve the planned plans was studied. Aspects of the enterprise's competitiveness are described, which makes it possible to increase existing resources and development directions, strengthening the enterprise's resource potential and reducing production costs, improving product quality. The authors determined that competitive production is an effective means of reflecting the use of the enterprise's resource potential, and the basic concept of resource potential, which is the main category of resources, determines the preservation of the environment.  The company's resources are: preservation and sources of raw materials, materials, labor, property and money, a complex of tangible and intangible components that participate in the production process.The authors considered the component of the resource potential of the enterprise, which has the following types of resources: labor; financial; material (fixed funds and current assets); intangible; informativeWays to improve the efficiency of resource potential use are revealed. It has been studied that the resource potential is a system of resources used by the enterprise in a complex manner, which provides for the specific complementarity of certain resources of the enterprise's production. The growth of one individual resource in this system leads to a simultaneous increase in the amount of another resource.The authors point out that the role and significance of the company's potential within social production is very difficult to overestimate. The potential of the enterprise is a prerequisite for the acceleration of scientific and technical progress and socio-economic development of the state.In this article, the authors concluded that the formation of ways, the increase in the efficiency of the use of the enterprise's resource potential, should take place taking into account certain data, which must be determined as a priority, because they play a key role and condition the effective use of material and other types of resources.
Keywords: potential; formation; resources; efficiency; scientific progress; resource potential; competitiveness; economic essence; complex; competitive production